Diamond Blackfan Anemia at the Crossroad between Ribosome Biogenesis and Heme Metabolism - Deborah Chiabrando; Emanuela Tolosano (Advances in Hematology)
Diamond-Blackfan anemia (DBA) is a rare, pure red-cell aplasia that presents during infancy. Approximately 40% of cases are associated with other congenital defects, particularly malformations of the upper limb or craniofacial region. Mutations in the gene coding for the ribosomal protein RPS19 have been identified in 25% of patients with DBA, with resulting impairment of 18S rRNA processing and 40S ribosomal subunit formation. Moreover, mutations in other ribosomal protein coding genes account for about 25% of other DBA cases. Recently, the analysis of mice from which the gene coding for the heme exporter Feline Leukemia Virus subgroup C Receptor (FLVCR1) is deleted suggested that this gene may be involved in the pathogenesis of DBA. FLVCR1-null mice show a phenotype resembling that of DBA patients, including erythroid failure and malformations. Interestingly, some DBA patients have disease linkage to chromosome 1q31, where FLVCR1 is mapped. Moreover, it has been reported that cells from DBA patients express alternatively spliced isoforms of FLVCR1 which encode non-functional proteins. Herein, we review the known roles of RPS19 and FLVCR1 in ribosome function and heme metabolism respectively, and discuss how the deficiency of a ribosomal protein or of a heme exporter may result in the same phenotype.